The Role of the Business Analyst in Delivering Successful Digital Transformation Initiatives: An Advisory Services Perspective - Molekwa, Refilwe (University of the Witwatersrand, Johannesburg, 2023)
Digital transformation is a vital strategic imperative for organizations in today's fast-evolving digital landscape. Business analysts (BAs) play a crucial role in facilitating successful digital transformation initiatives. However, their roles remain undefined, leading to unexplored impacts on these initiatives. This study, involving 12 participants, aims to scrutinize the roles and challenges of BAs in the context of digital transformation. Drawing on extensive literature reviews and real-world case studies, the research assesses the specific contributions of BAs, challenges they encounter, stakeholder perceptions, and existing support mechanisms. It utilizes the Context, Content, Process, and Outcomes framework to comprehensively examine BAs' involvement in digital transformation projects. Structured interviews were conducted with experienced BAs from Entelect Software South Africa, offering in-depth insights into their responsibilities, challenges, and strategies throughout digital transformation journeys. The findings underscore the BAs' role as essential intermediaries who bridge the business-technology divide, facilitating effective communication, collaboration, and coordination among stakeholders. However, challenges such as resistance and technical knowledge gaps may hinder their ability to propose effective solutions. The study reveals that unclear expectations and adaptation struggles can result from misunderstandings of the BA role. Despite the growing recognition of their significance in digital transformation, ambiguity about their responsibilities persists
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Business analysis; Business analyst; Digital business; Digitalisation; Advisory services; UCTD; SDG-8: Decent work and economic growth